A randomised phase II study of oxaliplatin/5-FU (mFOLFOX) versus irinotecan/5-FU (mFOLFIRI) chemotherapy in locally advanced or metastatic biliary tract cancer refractory to first-line gemcitabine/cisplatin chemotherapy. (September 2021) - Choi, In Sil; Kim, Ki Hwan; Lee, Ju Hyun; Suh, Koung Jin; Kim, Ji-Won; Park, Jin Hyun; Kim, Yu Jung; Kim, Jin-Soo; Kim, Jee Hyun; Kim, Jin Won
Abstract: Background: In locally advanced or metastatic biliary tract cancer (BTC), second-line chemotherapy is challenging after progression from first-line gemcitabine/cisplatin. This study evaluated whether irinotecan/5-fluorouracil (5-FU; mFOLFIRI) was superior to oxaliplatin/5-FU (mFOLFOX) as a second-line treatment in BTC. Patients and methods: Patients diagnosed with BTC with disease progression after prior gemcitabine/cisplatin were randomised (1:1) to either mFOLFOX (control arm) or mFOLFIRI (experimental arm). Randomisation was stratified by tumour location (intrahepatic versus extrahepatic versus gallbladder versus ampulla of Vater) and ECOG performance status (0, 1 versus 2). The primary endpoint was the overall survival (OS) rate at 6 months. Results: In total, 120 patients were enrolled and 118 patients were randomised (mFOLFOX n = 59, mFOLFIRI n = 59). The baseline characteristics were well balanced between the two arms. The tumour location was intrahepatic bile duct in 48 patients (40.7%), extrahepatic bile duct in 29 patients (24.6%), gallbladder in 35 patients (29.7%) and ampulla of Vater in 6 patients (5.1%). At a median follow-up duration of 25.8 months, the 6-month OS rate was 54.1% in mFOLFOX and 44.1% in mFOLFIRI (p = 0.677). The median OS was 6.3 months (95% CI, 4.4–8.2) in mFOLFOX and 5.7 months (95% CI, 4.7–6.7) in mFOLFIRI (p = 0.677). The median progression-free survival was 2.8 months (95% CI, 2.3–3.3) in mFOLFOX and 2.1 months (95% CI, 1.1–3.1) in mFOLFIRI (p = 0.974). Of the 101 evaluable patients, the objective response rate and disease control rate were 5.9% and 66.7% in mFOLFOX and 4.0% and 64.0% in mFOLFIRI (p = 0.663 and p = 0.778, respectively). Peripheral neuropathy (37.5% versus 5.2%) and thrombocytopenia (35.7% versus 15.5%) in mFOLFOX and vomiting (19.0% versus 1.8%) and cholangitis (10.3% versus 0.0%) in mFOLFIRI occurred more frequently. No chemotherapy-related death was reported. Conclusion: In the second-line treatment of BTC, mFOLFIRI was not superior to mFOLFOX. However, mFOLFIRI was tolerable and showed comparable efficacy to mFOLFOX. Adverse events were different between the two arms. ClinicalTrials.gov Identifier: NCT03464968 Highlights: In second-line therapy for BTC, mFOLFIRI was not superior to mFOLFOX. However, the clinical efficacy of mFOLFIRI was comparable with that of mFOLFOX. The adverse events were different between mFOLFIRI and mFOLFOX. Therefore, mFOLFIRI could be an alternative regimen to mFOLFOX. mFOLFIRI could be the subsequent treatment after second-line mFOLFOX in BTC.